Esguitar wrote:
Hi,
Could someone tell me! what is wrong with my approach. I did that:
( 2^12 - 2^6 ) / ( 2^6 - 2^3 ) =
2^6 ( 2^2 - 1 ) / 2^3( 2^2 - 1 ) =
2^6 / 2^3 =
2^3
Answer D
Esguitar ,when you factored out \(2^6\) and \(2^3\), you divided the exponents instead of subtracting them. Easy mistake to make.
\(\frac{a^{12}}{a^{6}} = a^{12-6} = a^{6}\), and
\(\frac{2^{12}}{2^{6}} = 2^{12-6} = 2^{6}\)
So first factoring would be \(2^{6}(2^{6} - 1)\)
\(2^{12}\) = 4,096
\(2^6\) = 64
\(2^2\) = 4
64*4= 256, not 4,096
Hope it helps.
_________________
SC Butler has resumed! Get
two SC questions to practice, whose links you can find by date,
here.Instructions for living a life. Pay attention. Be astonished. Tell about it. -- Mary Oliver